PENGARUH LATIHAN SENAM AYO BERGERAK INDONESIA TERHADAP TINGKAT KEBUGARAN JASMANI SISWA PUTRA KELAS VIII SMP N 8 KOTA JAMBI - Deddy Rahmat Saputra (Jurnal Muara Olahraga, 2020)
Gymnastics is a sport that is carried out en masse, starting from the elementary, middle, upper, and public levels. In the past, gymnastics was very cultured, this is evidenced by the absence of differences in almost all circles of the gymnastics community both in groups and collectively, old, young, male, and female exercising together. This study aims to determine "The Effect of Indonesian Move Gymnastics Exercise on the Physical Fitness Level of Class VIII Boys of SMP N 8 Jambi City. This research is an experimental study conducted with the aim of knowing whether there is a consequence of something imposed on the sample to be studied. The research method used is an experimental method with a sample size of 36 people. The research method used is an experimental method with a sample size of 36 people. Before being given treatment, students began with (pretest), then were given treatment 16 times, after that, it ended with (posttest). This exercise is carried out for 6 weeks with a frequency of training 3 times a week. Based on the tests carried out, the following data were obtained, the initial test data for the average level of physical fitness was 12.83. Standard deviation 1.44. With the highest score of 16 and the lowest of 11. While the data for the final test, the level of physical fitness averaged 15.5. Standard deviation 1.34. With the highest score of 18 and the lowest of 13. The results of the analysis of the normality test for the initial test population obtained data L0 = 0.1357, L table = 0.1477. While the results of the analysis of the normality test for the final test population obtained data L0 = 0.1443, L table = 0.1477. Because L0 <Ltabel means that both data come from populations that are normally distributed. Homogeneity test results show Fcount (1.16) <Ftable (1.75), so the data is homogeneous. The -t test shows that there is a difference between (pretest) and (posttest) tcount (32.59)> ttable (1.689).The results of this study prove that gymnastics let's move in Indonesia can improve the physical fitness of male students with a fitness level of 2.67. Based on the results of the study, it can be concluded that there is a significant effect of Indonesian gymnastics exercises on the level of physical fitness of male students of class VIII SMP 8 Jambi City.